Efeito do scalping de quartzo grosso na flotação catiônica reversa de minério de ferro - Manoel Marques Braga Júnior (2010)
The size of the mineral particles present in the pulp is a relevant variable in the sequence of events resulting in flotation and affects significantly the process performance. The kinetic behavior of coarse particles is slower and they require longer residence time in the reactor, while fine particles interfere with the selectivity in the system. The effect of scalping the coarse quartz particles prior to flotation and its impact on thereduction of reagents specific consumption was investigated. Samples of the flotation feed at ITM-D (VALE-PICO) under different industrial operation conditions were collected. Flotation experiments were performed aiming at achieving enhanced conditions for a high recovery of coarse quartz particles. The comparison among the results of flotation tests in the presence and absence of coarse quartz particles in the pulp was positive, for the efficiency of coarse quartz scalping was observed (sample screened at 0.150mm). The results achieved with thepreviously screened sample were superior to those obtained with the global sample, namely: lower silica content in the concentrate, higher separation efficiency, higher selectivity index values, higher mass recoveries, lower iron grades in the tailings, and faster flotation kinetics.The indication was that the industrial future application of coarse quartz scalping is feasible yielding adequate flotation and reduction in the overall reagents costs.